2013
DOI: 10.1179/2042618612y.0000000020
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of clinical examination features for identifying large rotator cuff tears in primary health care

Abstract: Objectives: Rotator cuff tears are a common and disabling complaint. The early diagnosis of medium and large size rotator cuff tears can enhance the prognosis of the patient. The aim of this study was to identify clinical features with the strongest ability to accurately predict the presence of a medium, large or multitendon (MLM) rotator cuff tear in a primary care cohort. Methods: Participants were consecutively recruited from primary health care practices (n5203). All participants underwent a standardized h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 72 publications
(74 reference statements)
1
26
0
1
Order By: Relevance
“…Most diagnoses in the shoulder are based on the history and clinical examination alone and there is no objective gold standard to compare to for the most common diagnoses (39,40). The diagnoses osteoarthritis and full thickness rotator cuff tears require corresponding findings on imaging (41). We used a standardised diagnostic routine to identify the point prevalence of musculoskeletal diagnoses (appendix 1).…”
Section: Icd-10 Diagnosis With Descriptionmentioning
confidence: 99%
“…Most diagnoses in the shoulder are based on the history and clinical examination alone and there is no objective gold standard to compare to for the most common diagnoses (39,40). The diagnoses osteoarthritis and full thickness rotator cuff tears require corresponding findings on imaging (41). We used a standardised diagnostic routine to identify the point prevalence of musculoskeletal diagnoses (appendix 1).…”
Section: Icd-10 Diagnosis With Descriptionmentioning
confidence: 99%
“…This joint pain is usually persistent, producing a high disability in work activity and daily life. Furthermore, it is a major burden on health resources in Spain and leads to lost productivity due to absenteeism, as shown by Cadogan et al [33]. For these reasons, it is essential to develop intervention programs aimed to prevent these kind of pathologies as well as treat them [34].…”
Section: Discussionmentioning
confidence: 99%
“…Early identification of full-thickness and medium-to-largesized partial-thickness rotator cuff tears is important for primary care providers, as early identification will aid in optimizing outcomes (e.g., advanced imaging and surgical referral) [4]. The key for primary care providers in order to facilitate prompt identification of these injuries is obtaining a detailed history and performing an appropriate physical examination.…”
Section: The Initial Visitmentioning
confidence: 99%
“…The key for primary care providers in order to facilitate prompt identification of these injuries is obtaining a detailed history and performing an appropriate physical examination. Studies have shown that a history of nighttime pain, consistent pain, and older age are predictors of rotator cuff tears [4,5]. Co-morbidities including diabetes mellitus, high body mass index, oral corticosteroid use, Achilles tendinitis, carpal tunnel syndrome, and trigger finger have been associated with rotator cuff disease [6].…”
Section: The Initial Visitmentioning
confidence: 99%
See 1 more Smart Citation